The Effect of Regional Original Income, General Allocation Funds and Natural Resource Revenue Sharing Funds on Capital Expenditure - Endang Ruhiyat; Wuri Handayani (EAJ (Economic and Accounting Journal), 2021)
The purpose of this research is to analyze Regional Original Revenues, General Allocation Funds and Natural Resource Revenue Sharing Funds on Capital Expenditures local government in the province of Banten in the past 10 years. The research design used in this study is an associative method. The analytical model used is quantitative. The variables used are Regional Original Revenues, General Allocation Funds and Natural Resource Revenue Sharing Funds as independent variables and Capital Expenditures as the dependent variable. The sample used in the budget realization report for 10 years from 2011 to 2020. The data analysis technique used is descriptive statistics and panel data regression analysis using Eviews 9 software. The analytical tool used is the Panel Data Regression Model Selection, Classical Assumption Model, Determination Coefficient, F Test and t-Test. Based on the results of the study it was found that (1) Regional Original Revenues, General Allocation Funds and Natural Resource Revenue Sharing Funds show together have an effect Capital Expenditures; (2) Regional Original Revenues partially has no effect Capital Expenditures; (3) General Allocation Funds partially has no effect Capital Expenditures; (4) Natural Resource Revenue Sharing Funds partially has no effect Capital Expenditures